Patent Research as a Tool for Analysis of the Technical Solutions Market - M. S. Ryabokon (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The example of the analysis of patent activity shows the solution of the problem related to the assessment of the development potential of technical systems. The main possibilities of modern information resources of patent analytics are described. It is shown how the analysis of patent information helps to select the most promising scientific and technical solutions and technologies for development, to identify trends in the industry, to analyze the market situation to determine the main competitors and partners, to assess the competitiveness of the developed products, to form requirements and to draw up a plan for research and development, to develop a strategy for innovative development of the enterprise.